Perspektif Masyarakat terhadap Konten TikTok Anak Berkebutuhan Khusus (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Children with special needs are children who require special treatment due to developmental disorders and abnormalities experienced by the child. This study is a quantitative descriptive study that aims to explore the public's perspective on TikTok content for children with special needs. Using a sample of 70 respondents selected through simple random sampling techniques, this study found that most respondents had seen children with special needs on TikTok and felt touched when they saw content for children with special needs. The majority of respondents also thought that children with special needs deserved to be made into content and could influence public perception of children with special needs. This study also shows that content for children with special needs on TikTok can increase public empathy for children with special needs and be an inspiration for the public. The results of this study can be a reference for increasing public awareness and understanding of children with special needs and the importance of inclusion on social media. Thus, the TikTok platform can be an effective means of promoting inclusion and public understanding of children with special needs.